CONTAMINATION OF ANIMAL PRODUCTS BY RESIDUAL QUANTITY OF ANTIBIOTICS - Vistovskaya, V. P.; Zaugolnikova, M. A. (Acta Biologica Sibirica, 2016)
The use of antibiotics in animal results in a number of negative aspects, both for animals and humans using animal food products. One of the reason of this is the ignorance of time required to eliminate the antibiotics from the body when using meat, milk and eggs after antibiotic therapy of animals. That is why the residual amount of antibiotic substances is strictly standardized in livestock production. The article presents the data showing that tetracycline exceeds maximum allowable concentration towards the detected antibiotics (streptomycin, tetracycline, sulfonamides, chloramphenicol).